2010
DOI: 10.3922/j.psns.2010.2.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on pentylenetetrazole-induced anxiety-like behaviors and associated changes in cognition and monoamine levels.

Abstract: The purpose of the present study was to estimate the protective effects of curcumin against anxiety and memory impairment, which are often comorbid in patients with anxiety disorders who are on standard anxiolytic therapy. The effects of curcumin on brain monoamine levels were also determined. We used the elevated plus maze (EPM), a standard animal model of anxiety, to determine the effects of subacute administration (14 days) of curcumin at doses of 5 and 10 mg/kg (p.o.) against pentylenetetrazole (PTZ; 20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Anxiogenic behavior was also exhibited by D-gal administrated rats in LDT as evident from less time spent and fewer entries in the light compartment. Although in the present study it is difficult to justify the depressogenic and anxiogenic effects in terms of brain 5-HT levels, however, the anxiogenic effects produced by D-gal may possibly be due to decreased levels of 5-HT in brain which cause an upregulation of post synaptic 5-HT2C anxiogenic receptors that may lead to anxiogenic symptoms [14,44]. Another cause could be that overwhelming D-gal may also lead to metabolic stress which probably may result in anxiety like behavior [10].…”
Section: Discussionmentioning
confidence: 74%
“…Anxiogenic behavior was also exhibited by D-gal administrated rats in LDT as evident from less time spent and fewer entries in the light compartment. Although in the present study it is difficult to justify the depressogenic and anxiogenic effects in terms of brain 5-HT levels, however, the anxiogenic effects produced by D-gal may possibly be due to decreased levels of 5-HT in brain which cause an upregulation of post synaptic 5-HT2C anxiogenic receptors that may lead to anxiogenic symptoms [14,44]. Another cause could be that overwhelming D-gal may also lead to metabolic stress which probably may result in anxiety like behavior [10].…”
Section: Discussionmentioning
confidence: 74%
“…(28) This latter finding on the enhancement of serotonin and norepinephrine by curcumin is of particular importance due to the important role of these neurotrransmitters in mood regulation. (37) The serotonergic system plays a crucial role in the pathogenesis of neuropsychiatric disorders.…”
Section: Baselinementioning
confidence: 94%
“…Inspite of the preclinical evidence that exists on the anti-depressant and anti-anxiety activities of curcumin, (26)(27)(28) there is a lack of scientific evidence on its clinical efficacy. Furthermore, curcumin is reported to possess anti-obesity effects which due to the close relationship between obesity and psychiatric disorders, could lead to the improvement of psychiatric disorders.…”
mentioning
confidence: 96%
“…These have consistently demonstrated that both acute (Arora et al, 2011;Chimakurthy and Talasila, 2010;Gilhotra and Dhingra, Antidepressant Potential Modes of Action of Curcumin 2010; Kulkarni et al, 2008;Sanmukhani et al, 2011;Wang et al, 2008) and chronic (Bhutani et al, 2009;Huang et al, 2011;Li et al, 2009;Sanmukhani et al, 2011;Xia et al, 2007;Xu et al, 2005b) administration of curcumin to rats and mice reduces immobility time.…”
Section: Antidepressant Effects Of Curcumin In Animal Modelsmentioning
confidence: 99%